Effect of adding durian seed flour (Durio zibethinus Murr.) on the setting time of alginate impression material: an experimental laboratory study - Fransiska, Aria; Isnain, Zahrotus Shobah; Ramayanti, Sri; Yohana, Nelvi; Cahyanto, Arief (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2025)
Introduction: Alginate is one of the most commonly used impression materials in dentistry to obtain a negative reproduction of teeth and surrounding tissues. To achieve an accurate impression, alginate must have an adequate setting time. However, its tendency to set too quickly is one of the material’s main weaknesses in clinical use. Modification of alginate with durian seed flour (Durio zibethinus Murr.), which contains amylose and amylopectin, may alter its setting time. This study aimed to analyze the effect of adding durian seed flour on the setting time of alginate impression material. Methods: This was an experimental laboratory study using a post-test only control group design. The samples consisted of pure alginate and alginate mixed with 20% and 40% durian seed flour, for a total of 30 samples. The setting time was measured using a cylinder rod tip and recorded with a stopwatch. Data were analyzed using One-way ANOVA followed by Post Hoc LSD tests. Results: The mean setting times of pure alginate, alginate 80% + durian seed flour 20%, and alginate 60% + durian seed flour 40% were 132.2 ± 3.495 s; 212.3 ± 3.742 s; and 266.8±3.369 s, respectively. The addition of durian seed flour significantly affected the setting time of alginate impression material (p<0.05). Conclusion: Alginate with 40% durian seed flour addition exhibited the longest setting time compared with other sample groups. However, alginate with 20% and 40% durian seed flour additions still met the American Dental Association (ADA) Specification No. 18 for acceptable setting time.Pengaruh penambahan tepung biji durian (Durio zibethinus Murr.) terhadap setting time bahan cetak alginat: eksperimental laboratorisPendahuluan: Bahan cetak alginat merupakan bahan cetak yang paling sering digunakan di kedokteran gigi untuk mendapatkan reproduksi negatif gigi dan jaringan disekitarnya. Alginat harus memiliki setting time yang cukup agar dapat menghasilkan cetakan yang baik. Setting time yang cenderung terlalu cepat menjadi salah satu kelemahan alginat dalam keadaan klinis. Modifikasi alginate dengan penambahan tepung biji durian yang memiliki kandungan amilosa dan amilopektin dapat mempengaruhi setting time alginat. Tujuan menganalisis pengaruh penambahan tepung biji durian (Durio zibethinus Murr.) terhadap setting time bahan cetak alginat. Metode: Penelitian ini menggunakan jenis penelitian experimental laboratory dengan desain penelitian post-test only control group design. Sampel yang digunakan dalam penelitian ini adalah bahan cetak alginat murni serta alginat dengan penambahan tepung biji durian 20% dan 40%. Total sampel keseluruhan sebanyak 30 sampel. Setting time diukur dengan ujung batang silinder dan dihitung menggunakan stopwatch. Data hasil penelitian dianalisis menggunakan uji One Way ANOVA dan Post Hoc LSD. Hasil: Rata-rata hasil pengukuran setting time alginat murni, alginat 80%+tepung biji durian 20%, alginat 60%+tepung biji durian 40% berturut-turut adalah: 132,2±3,495; 212,3±3,742; 266,8±3,369. Penelitian ini menunjukkan bahwa penambahan tepung biji durian berpengaruh terhadap setting time bahan cetak alginat (p<0,05). Kesimpulan: Alginat dengan penambahan tepung biji durian 40% memiliki setting time yang paling lama dibandingkan dengan kelompok sampel lainnya pada penelitian ini. Alginat dengan penambahan tepung biji durian 20% dan 40% memiliki setting time yang masih sesuai dengan standar American Dental Association (ADA) No. 18.